Exploiting the Unbanked: Evidence from Singapore's Unlicensed Moneylending Market - Kaiwen Leong; Huailu Li; Haibo Xu (Institute of Labor Economics (IZA), 2018)
Using a unique dataset covering the borrowing behaviour of over a thousand borrowers, we study the unlicensed moneylending market in Singapore. In this market, borrowers search for lenders, and lenders decide how much profit to extract from borrowers. Lenders harass borrowers into compliance. We observe that different lenders apply different markups on different borrowers. Higher markups discourage borrowers from repeatedly borrowing from a particular lender. Increased enforcement specifically targeted at reducing the number of lenders in this market will increase markups, but will not deter borrowers from becoming recurrent borrowers because they have fewer lenders to choose from.
Keywords: K42; 330; illegal lending; enforcement; markup